The Effectiveness of ICL Implantation in Treating Moderate to High Myopia: Analyzing Changes in Anterior Chamber Parameters - Ankit S Varshney; Rumana Z Patel; Najwa Mansuri (GAIMS Journal of Medical Sciences, 2025)
Background: This study aims to assess the efficacy and safety of implantable collamer lens (ICL) implantation in correcting moderate to high myopia, with a particular focus on its impact on anterior segment parameters, including anterior chamber depth (ACD), intraocular pressure (IOP), and endothelial cell density.